Penerapan Teori Belajar Bermakna David Ausubel dalam Meningkatkan Pemahaman Konseptual Siswa - Indah, Annisa; Abimanyu, Aditya (Department of Educational Technology, Postgraduate Program, State University of Makassar, 2025)
This study examines how the application of meaningful learning theory, developed by David Ausubel, can improve students' concept understanding. The theory emphasizes the importance of fitting new information into existing cognitive frameworks, allowing for deeper and longer-lasting understanding. Concepts such as advance organizers, progressive differentiation, knowledge assimilation, and integrative reconciliation are applied to support a more effective learning process. This research uses the literature study method by elaborating on various related sources to gain a thorough understanding of implementing this theory in Indonesia's education context. The results show that applying meaningful learning theory strengthens students' conceptual understanding and encourages the development of critical, creative, and adaptive thinking skills. Therefore, teachers are encouraged to integrate this approach in lesson planning and implementation to make students' learning experiences more relevant, applicable, and meaningful.